1st International Hydrographic Technical Conference, May 14-18, 1979, Ottawa, Canada : proceedings - International Hydrographic Technical Conference (1st : 1979 : Ottawa, Canada) (Ottawa : Canadian Institute of Surveying, 1979)
27